2020
DOI: 10.1155/2020/3484718
|View full text |Cite
|
Sign up to set email alerts
|

Root Tensile Resistance of Selected Pennisetum Species and Shear Strength of Root-Permeated Soil

Abstract: It is widely recognized that vegetation plays a significant role in contrasting slope instability through the root reinforcement. The main objectives of this paper are to evaluate the root tensile of selected Pennisetum species, namely, P. pedicellatum (PPd) and P. polystachion (PPl), and to determine the soil shear strength of root-permeated soil from these species. The selected species were initially planted in the polybags using the hydroseeding technique. A mineral fertilizer of NPK ratio 10 : 8 : 10 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Root tensile resistance and root distribution play a critical role in soil conservation and slope stability [44][45][46]. Our results demonstrated that root tensile resistance and root configuration varied notably between these two species.…”
Section: Root Tensile Strengthmentioning
confidence: 65%
“…Root tensile resistance and root distribution play a critical role in soil conservation and slope stability [44][45][46]. Our results demonstrated that root tensile resistance and root configuration varied notably between these two species.…”
Section: Root Tensile Strengthmentioning
confidence: 65%
“…According to Comino & Marengo (2010) effective root reinforcement can be measured through soil shear strength, root tensile strength and root architecture. Therefore, root tensile strength was expressed as a ratio of resistance and root area equation 2 which is measured as the ratio of maximum force applied to a root at the failure surface to its root diameter (Ettbeb et al, 2020;Lee et al, 2020). a one-way ANNOVA was conducted to test for differences within species.…”
Section: Tree Species Root Characteristics For Slope Stabilitymentioning
confidence: 99%
“…However, this method was modified to mean diameter of horizontal roots and mean DBH presented in equation 4. The overall root reinforcement was determined using the soil shear strength calculated from equation 5 below ( Yu et al, 2020;Ettbeb et al, 2020;Sofia & Afonso, 2019;Comino & Marengo, 2010) which then descriptive statistics followed…”
Section: Tree Species Root Characteristics For Slope Stabilitymentioning
confidence: 99%
“…This resulted from the two species of grass Kolonjono and Gajah grass, which functions to reduce the rainfall as well as runoff energy. Gajah grass (Pennisetum purpureum) is one of the plants that can control erosion [20].…”
Section: A Erosion Ratesmentioning
confidence: 99%